Outcome of a Resident Spine Surgical Skills Training Program. Issue 8 (October 2017) - Calio, Brian P.; Kepler, Christopher K.; Koerner, John D.; Rihn, Jeffrey A.; Millhouse, Paul; Radcliff, Kris E.
Abstract : Study Design: Cadaver training lab. Objective: To determine if a technical cadaver skills training lab for spinal surgery increases resident confidence, satisfaction in training, and perception of operating room safety. Summary of Background Data: Resident training is an important topic in the setting of work hour reform. The use of supplemental materials such as videos, sawbones, and simulators may become important to adequately train orthopedic residents. At present, there are no established curricula for training orthopedic surgery residents on anatomy and common procedures encountered during a spinal surgery rotation. Methods: Residents were assembled into teams of a PGY-5 and PGY-2 and/or PGY-1 to perform dissection and procedures on 5 fresh-frozen spine cadavers. With attending and spine fellow supervision, residents performed anterior cervical, posterior cervical, and posterior thoracolumbar surgical exposure, decompression, and fusion procedures in the operating room using surgical tools and instrumentation. Residents were then queried about their confidence levels, satisfaction in training, and perception of safety using a Likert scale (0–10). Strong agreement (scores ≥8) and strong disagreement (scores ⩽3) and correlations were evaluated. Results: Seventeen residents completed the training program (7 PGY-1s, 2 PGY-2s, and 8 PGY-5s). After the training, the majority of residents strongly agreed that they had an increased confidence of their own abilities (59%). A significant majority (65%) of residents strongly agreed that they were satisfied with the benefits provided by the training program. Compared with other methods of education, residents strongly agreed that the training was more helpful than textbook chapters (94%), sawbones (94%), web-based training (94%), or a virtual-based (completely electronic) training (94%). After the training, residents strongly agreed that the training improved feelings of preparation (47%), safety (41%), and ability to prevent intraoperative errors (41%). The vast majority of residents strongly agreed "Before performing surgery on me, I would want a resident to perform this cadaveric training" (88%). Conclusions: These results demonstrate that team-based, cadaveric training with adequate attending supervision, before onset of a spine surgical rotation, may lead to high resident confidence, satisfaction in training, and perception of patient safety.